Corporate Social Responsibility Reporting on Websites in Thailand - Suttipun, Muttanachai; Nuttaphon, Cholticha (Kasetsart Journal of Social Sciences, 2014)
This study aimed to investigate the extent and nature of corporate social responsibility reporting (CSRR) on the websites of companies listed on the Stock Exchange of Thailand (SET), and to examine the factors influencing the amount of CSRR on those websites. The population of this study was all the companies listed on the SET. By using quota sampling, 221 firms were selected as the research sample. Content analysis was used to quantify the CSRR on the websites of the sample. Descriptive analysis and multiple regression were used to analyze the data. This study found that 138 firms (65 %) provided CSRR on their websites. Companies in the natural resource sector disclosed the most CSRR on their websites with the consumer products sector providing the least. Significant relationships were found between the amount of CSRR on websites and the size of the company, the type of auditor, liquidity, and ISO standards. The usual limitations associated with sampling, and content analysis apply and the study did not consider the issue of the quality of the reporting on websites. This study is the first study of website-based CSRR by Thai companies. It also refutes previous statements in the literature that companies in developing countries are ignorant of the use of this technology.